Voluntary work and its role in the development of the local community A survey study on charities in Abha city - Albusilee, Mohammed Jibril (Journal of Humanities & Social Sciences, 2022)
This study aimed at the reality of volunteer work and requests for development, and what is its role and contribution to achieving development in all its fields of the most prominent obstacles that it faces and limits the local community in the city of Abha from the point of view of volunteers and volunteers in charitable societies in the city of Abha. With a proposal to activate it. This study was a descriptive and analytical study based on the comprehensive social survey method, as it was applied to all male and female volunteers in charitable societies in the city of Abha. The size of the study population was (361) male and female volunteers. The questionnaire tool was used. The data was analyzed using the Statistical Packages Program (SPSS) and the most important results showed that volunteer work in the local community in Abha city is practiced at a (high) degree. The results also showed that the material - human - organizational obstacles facing volunteer work and limiting its role in the development of the local community in the city of Abha with a (high) degree of disability. It was found that the organizational obstacles had the highest arithmetic average compared to the rest of the obstacles. It also became clear that the most important requirements for activating and developing volunteer work were (the importance of honoring volunteers and motivating them to urge them to give more to contribute to the development of their community, as well as the very great need for clarity of legislation and regulations for volunteer work).
Keywords: Volunteer work; Social development; Local community